PENGATURAN PRAKTIK PEKERJA SOSIAL PROFESIONAL DI INDONESIA - Astri, Herlina (Jurnal Aspirasi, 2013)
Professional Social Workers (Social Workers) in Indonesia is not widely demonstrated its role yet. Besides not widely recognized as a professional profession who has specific standards, the institutional existence of Social Workers also have not much seen. Social Workers in Indonesia have not received assurance of legal protection in practice. This study uses literature study to examine further clarity on the legal protection of Social Workers professional practice. It is very important to ensure the professionalism, effectiveness, and accountability of social services provided.